A Study On Cyp2c19 Genetic Variations Of Clopidogrel And Ticagrelor Treatment Among Coronary Artery Disease (CAD) Patients Undergoing Percutaneous Coronary Intervention (PCI) - Ak-Kaif, Mohammed Ahmed Imran (2023)
The P2Y12 receptor inhibitors, especially clopidogrel, are common antiplatelet drugs used for the prevention of recurrent adverse cardiovascular events among patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). Several factors may affect the effectiveness of antiplatelet therapy, including genetic variations in CYP450 enzymes. Loss of function (LOF) carriers of the CYP2C19 gene are associated with the decreased metabolism of clopidogrel into active metabolites via CYP2C19 enzyme, leading to decreased platelet inhibition. This causes an increased risk of recurrent cardiovascular events. Drug regulatory authorities suggested using alternative P2Y12 inhibitor, which is ticagrelor. Therefore, this study aims to investigate the adverse effects, and CYP2C19 genetic variations of clopidogrel and ticagrelor treatment among CAD patients undergoing PCI.